A Critical Case Of Closed Cervix Pyometra In A Bitch - Agrawal, Jitendra Kumar; Saxena, Atul; Patel, Akhil; Kumar , Pramod (Indian Journal of Veterinary Sciences and Biotechnology, 2016)
Pyometra is accumulation of purulent material within the uterus, which manifests in both local and systemic symptoms, and demands costly surgical or medical intervention (Hagman et al., 2011). Pyometra is typically a post-oestral syndrome in adult bitches associated with a variety of clinical and pathological manifestations of genital and multisystemic disease. Uterine exposure to progesterone during canine dioestrus plays a key role in the pathogenesis of the disease. Progesterone induces changes in the uterus which prepare a suitable environment for early embryo development, including endometrial proliferation, increased uterine glandular secretions and decreased myometrial contractions, as well as a relaxation in normal uterine cellular immune defences (Noakes et al., 2009). It is postulated that intrauterine bacteria, which ascend from the vagina during pro-oestrus and oestrus, induce the disease during metoestrus by acting on the progesterone-primed endometrium directly via toxin production, or indirectly by the release of inflammatory mediators (Noakes et al., 2001). Parity and age are significant risk factors in the development of pyometra (Niskanen and Thrusfield, 1998).This case report communicates the successful management of a critical case of closed cervix pyometra in a German shepherd bitch.